Mathematical mindset shift: reducing math anxiety and enhancing attitudes in secondary school students through growth mindset intervention - Noor Atiqah Mohd Noh; Aini Marina Ma'rof; Yusni Mohamad Yusop (Institute of Advanced Engineering and Science, 2026)
This study examines the effectiveness of a growth mindset intervention (GMI) in improving mathematical mindset, reducing math anxiety, and enhancing attitudes toward mathematics among secondary school students. A true-experimental design was employed, involving 69 Form Two students from secondary schools in Kedah, Malaysia. Participants were randomly assigned to a treatment group (n=35) or a control group (n=34). Data were analyzed using multivariate analysis of covariance (MANCOVA). The results revealed significant differences in math anxiety (p=0.000) and attitudes toward math (p=0.000) between the treatment and control groups after controlling for covariates (math scores and gender). However, no significant difference was observed in mathematical mindset between groups (p=0.292). Within the treatment group, significant improvements were noted in mathematical mindset (p=0.001), math anxiety (p=0.000), and attitudes toward math (p=0.000), while the control group showed no significant changes across these variables. Students in the treatment group experienced reduced math anxiety and improved attitudes toward math following the intervention. These findings suggest that GMI is an effective strategy for mitigating math anxiety and fostering positive attitudes toward mathematics, providing valuable insights for educators seeking to improve students' learning experiences and outcomes.